TINJAUAN KADAR ASPAL AC-BC PADA RUAS JALAN RIVERSIDE MENGGUNAKAN METODE CENTRIFUGE EKSTRACTION - Ilyas Ichsan (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
Then findings pf ectraction gradation in table reveal that there is an asphalt is used ≥ and ≤ plan asphalt content in mixig JMF (Job Mix Formula) / so the rules is not appropriate with the specification. It shows that the laston mix will be influence. The findings of asphalt content or ectraction reveal that the mix of AC-BC which used in the field each point/sta. The collection sample score is still above and less from the specification requirement of JMF (Job Mix Formula) which is 5,75 %.